The Effect of Nutrition Education with Monopoly and Leaflet on The Nutritional Knowledge Levels and Consumption Pattern Among 5th Grade Elementary School Students in Surabaya - Rizki Nurmalya Kardina; Nimas Ayu Rengganis; Nurul Kamariyah (Jurnal Ilmiah Kesehatan, 2022)
In this era, many school-age children have unbalanced and unhealthy eating behaviors. Low nutritional knowledge levels cause the issues. This paper analyzes the differences in nutritional knowledge levels and consumption patterns before and after nutrition education with monopoly media and leaflets among 5th-grade elementary school students in Surabaya. The research method used a quasi-experimental design. The population was 170 5th grade elementary school students at SDN I and SDN II Surabaya. In addition,  this study utilized probability sampling with a sample of 90 students. Next, data analysis used the Mann-Whitney and Wilcoxon tests with a significant level of α 0.05. There were differences in nutritional knowledge levels before and after nutrition education with monopoly media in both schools (p=0.000). Meanwhile, there were no differences in nutritional knowledge levels before and after nutrition education with leaflet media (SDN I Surabaya p=0.073 and SDN II Surabaya p=0.052). In addition, both schools had differences in consumption patterns before and after nutrition education with monopoly media (p=0.000). However, there were no differences in consumption patterns before and after nutrition education with leaflet media (at SDN I Surabaya p=0.301 and SDN II Surabaya p=0.307). Nutrition education with monopoly media is more effective in improving nutritional knowledge levels and consumption patterns than leaflet media in 5th-grade students. Further research could compare monopoly with other EGT (educational game tools, such as snakes and ladders nutrition or nutrition puzzle.